2012
DOI: 10.1177/175114371201300412
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to the Difficult-to-Wean Patient

Abstract: The difficult-to-wean patient represents 6% of the intensive care population, but consumes a third of resources. Such patients experience increased morbidity and mortality. Given the changing demographics of intensive care practice, this patient group is likely to grow. Hitherto management of the difficult wean is rarely debated, though there exists a clear demand for further exploration. Here we present often overlooked, modifiable patient factors to optimise the chance of weaning success. The mechanism of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The guidelines for weaning from ventilator were developed 10 years ago, 1 which required the patient to meet adequate criteria. 61 However, traditional weaning parameters are not good predictors of a successful outcome in neurocritical care; for this reason, these parameters are not reliable in neuroemergencies. 62 In a multicenter observational study, 37 which included patients with TBI, stroke, and subarachnoid hemorrhage, showed that the duration of MV is greater, compared with other groups of patients in the ICU presenting greater challenges to the clinician for weaning in the neurological patients.…”
Section: Complicationsmentioning
confidence: 99%
“…The guidelines for weaning from ventilator were developed 10 years ago, 1 which required the patient to meet adequate criteria. 61 However, traditional weaning parameters are not good predictors of a successful outcome in neurocritical care; for this reason, these parameters are not reliable in neuroemergencies. 62 In a multicenter observational study, 37 which included patients with TBI, stroke, and subarachnoid hemorrhage, showed that the duration of MV is greater, compared with other groups of patients in the ICU presenting greater challenges to the clinician for weaning in the neurological patients.…”
Section: Complicationsmentioning
confidence: 99%
“…Infection And fluid accumulation is the main cause of death in ESRD patients. [1][2][3][4][5][6][7] Mechanical ventilation can complicate weaning due to various reasons, including weakness muscle, enhancement burden respiration, disturbance drives ventilation, disturbance oxygen carrying capacity, cardiac dysfunction and disturbance of sputum cleaning. [1,6,8] Other predictor of weaning complication is old age, long mechanical ventilation usage, lung infection or history of chronic obstructive pulmonary disease and positive fluid accumulation balance.…”
Section: Introductionmentioning
confidence: 99%
“…includes patients who require more than seven days after the first breathing trial [2]. Although difficult-to wean patients represents about 6 % of the patients inside the intensive care unit , they consume a third of resources [3] .…”
Section: Introductionmentioning
confidence: 99%